Hemodynamics and Diastolic Function after Native Aortic Valve Preserving vs. Replacing Surgery - Holst, Theresa; Hua, Xiaoqin; Sinning, Christoph; Waschki, Benjamin; Reichenspurner, Hermann; Girdauskas, Evaldas; Petersen, Johannes (The Thoracic and Cardiovascular Surgeon, 2023)
Background Alterations in left ventricular (LV) diastolic function following native tissue-preserving aortic valve (AV) procedures have not been systematically investigated. Furthermore, no comparisons have been made between these changes and those observed after prosthetic AV replacement.Methods From October 2017 to August 2020, 74 patients aged <65 years were referred to our institution for elective AV surgery. Preoperative and postoperative (i.e., discharge, 3-month and 1-year follow-up) transthoracic echocardiography was analyzed.Results Native tissue-preserving surgery was performed in 55 patients (AV repair: n = 42, Ross procedure: n = 13). The remaining 19 patients underwent prosthetic AV replacement. Preoperatively and at discharge, transvalvular hemodynamics and LV diastolic function were comparable in both groups. At 1-year follow-up, native valve (NV) patients showed significantly lower mean transvalvular gradient (7 ± 5 vs. 9 ± 3 mmHg, p = 0.046) and peak velocity (1.74 ± 0.51 vs. 2.26 ± 0.96 m/s, p = 0.004), and significantly better septal e′ (9.1 ± 2.7 vs. 7.7 ± 2.5 cm/s, p = 0.043) and lateral e′ (14.7 ± 3.1 vs. 11.7 ± 3.7 cm/s, p = 0.001). From preoperatively to 1-year postoperatively, septal and lateral e′ and E/e′ improved markedly after NV preservation (septal e′: +0.7 cm/s, p = 0.075; lateral e′: +2.3 cm/s, p < 0.001; E/e′: −1.5, p = 0.001) but not after AV replacement (septal e′: +0.2 cm/s, p = 0.809; lateral e′: +0.8 cm/s, p = 0.574; E/e′: −1.2, p = 0.347). Significant negative linear correlations between postoperative transvalvular gradients and absolute changes in lateral e′ and E/e′ were detected during follow-up.Conclusion Preservation of native tissue in AV surgery results in superior transvalvular hemodynamics compared with prosthetic AV replacement. This may induce faster LV reverse remodeling and may explain more pronounced improvement in LV diastolic function.
Keywords: aortic valve and root; heart valve surgery; cardiac